PHYSICAL AND CHEMICAL CHARACTERISTICS OF COMPOST, HUSK CHARCOAL AND WOOD CHARCOAL TO AMMONIA GAS ABSORPTION - Mohamad Yani; Mia Juliana (Department of Agroindustrial Technology, Bogor Agricultural University, 2012)
Ammonia is an odorous gas emitted from many industries and natural activities. The ammonia pollutant was treated by physical and chemical absorptions and biological oxidation (biofiltration). The objective of this research was to determine the physical and chemical characteristics of bokashi compost, husk charcoal, and wood charcoal and their composition by weight (K). This packing materials were analyzed to physical and chemical characteristics, such as moisture content, density, porosity, C/N ratio, water absorption capacity (WAC), and ammonia absorption capacity (AHC). The characteristics of husk charcoal were better than those of wood charcoal and compost. The husk charcoal had moisture content of 7%, density of 136 kg/m3, porosity of 86%, pressures drops of 434 Pa, C/N ratio of 41.60, WAC of 51%, AAC of 1.5x10-3g-N/g-dry-material, its saturated with ammonia for 5 hours and it was needed 30 minutes to detached the ammonia. The composition of packing materials of K122 and K221 were better than that of K212 or K221. The K122 had density of 220 kg/m3, porosity of 78%, pressure drops of 643 Pa, C/N ratio of 35, moisture content of 19%, WAC of 49%, AAC of 4.7x10-3g-N/g-dry-material, saturated with ammonia for 4 hours. The K221 had density of 247 kg/m3, porosity of 77%, pressure drops of 627Pa, C/N ratio of 36, moisture content of 26%, WAC of 17%, AHC of 4.3x1-5g-N/g-dry-material, saturated with ammonia for 6 hours. The physical and chemical characteristics of husk charcoal single or mixed packing materials influenced by the water and ammonia holding capacity. However, compost addition would support the microbial growth in biofilter. Keywords: ammonia absorbtion, compost, husk charcoal, wood charcoal